IMPROVING AIRCRAFT PARTS DUE TO USING NANO-COMPOSITE AND MICRO-COMPOSITE MATERIAL - H. M. Boer (Научный вестник МГТУ ГА, 2017)
In this paper it is investigated how to make composite carbon nanofiber/ epoxy resin and carbon micro-fiber / epoxy resin. Also, these materials' features are compared and it is shown how effective and benefitial are the received products containing carbon nano- and micro-fibers.In this study, epoxy composites were prepared in order to improve their mechanical and electrical properties. Ergo, carbon nanofibers and carbon microfibers were used as fillers. On the one hand, purchased microfibers were incorporatedinto the epoxy resin to produce epoxy/carbon microfiber composites via mechanical mixing at 1800 rpm in different concentrations (0.0125, 0.0225, 0.05, and 0.1).On the other hand, carbon nanofibers were prepared via electrospining method at room temperature, then epoxy/carbon nanofiber nanocomposites were prepared at mixing temperature of 60 °C at 1200 rpm at different concentrations (0.0125, 0.05, and 0.1).Morphology of samples was investigated via Field Emission Scanning Electron Microscopy (FESEM). Mechanical properties of samples were investigated via tensile and bending tests. Tensile test results revealed that incorporation of 0.0125 wt% carbon naofibers increased the epoxy resins modulus about 200%. Bending strength of sample containing 0.1wt% carbon microfibers had the most increment (from 20 to 100 MPa).